New Options for Vascularized Bone Reconstruction in the Upper Extremity - Houdek, Matthew T.; Wagner, Eric R.; Wyles, Cody C.; Nanos, George P., III; Moran, Steven L. (Seminars in Plastic Surgery, 2015)
Originally described in the 1970s, vascularized bone grafting has become a critical component in the treatment of bony defects and non-unions. Although well established in the lower extremity, recent years have seen many novel techniques described to treat a variety of challenging upper extremity pathologies. Here the authors review the use of different techniques of vascularized bone grafts for the upper extremity bone pathologies. The vascularized fibula remains the gold standard for the treatment of large bone defects of the humerus and forearm, while also playing a role in carpal reconstruction; however, two other important options for larger defects include the vascularized scapula graft and the Capanna technique. Smaller upper extremity bone defects and non-unions can be treated with the medial femoral condyle (MFC) free flap or a vascularized rib transfer. In carpal non-unions, both pedicled distal radius flaps and free MFC flaps are viable options. Finally, in skeletally immature patients, vascularized fibular head epiphyseal transfer can provide growth potential in addition to skeletal reconstruction.
Keywords: vascularized bone graft; vascularized fibula; medial femoral condylar flap; bone graft; vascularized epiphyseal transfer